National Banks: How Much do they Bank on Off Balance Sheet Items? An Indian Outlook - Gurjar, Hariom; Joshi, Mahesh Chandra; Tripathi, Akhilesh (Indian Journal of Finance, 2019)
The banking system forms the backbone of the financial sector in a bank-based economy such as India. Off-balance sheet activity plays a vital role in helping banks limit long-term financial resources in the balance sheet report and increase the banks' profitability worldwide. We explored the determinants of OBS items with banking and economic factors influencing off-balance items in the measurement of banks' output of selected national banks in India for the duration of 2008-2017. This study used a multiple regression model to describe the logical connection between the role of OBS and its various determinants like bank size, loan, CAR, NNPA, NIM, ROA, reserves, GDP, and inflation for the said period. This study found that bank size and NIM positively affected the OBS activities; whereas, CAR and loan negatively affected the OBSA of the selected public sector banks.